Radiological manifestations of benign mesenteric lipoma that presented with acute intestinal obstruction: a case report - Eng, David Yeow Gan; Wei, Woon Teng; Theva Darshini Surenthiran; Chiak, Yot Ng; Mohd Firdaus Mohd Hayati (The Egyptian Society of Radiology and Nuclear Medicine, 2022)
Background: Intestinal obstruction is a common surgical emergency that is presented to the hospital with various aetiologies. Among all, mesenteric lipoma is one of the uncommon extraluminal causes of intestinal obstruction. In such conditions, bowel volvulus, compression or even adhesion are the underlying pathologies. Case presentation: We report a 69-year-old gentleman who presented with a triad of intestinal obstruction which required exploratory laparotomy. Preoperative computed tomography revealed multiple coalescing lobulated hypoattenuating lesions encircling part of a small bowel forming transitional zone. These lesions are comparatively more hypoattenuating in comparison with the surrounding mesenteric fat. Intraoperatively, a giant ileal mesenteric lipoma was identified causing compression and folding to the adjacent small bowel, leading to proximal bowel dilatation. Excision of the lipoma with a few mesenteric lymphadenectomy was done, revealing a benign mesenteric lipoma and reactive lymph nodes. Despite ileus, he made a good postoperative recovery and was discharged well. Conclusions: Patients with recurrent abdominal pain must have a thorough endoscopic and imaging assessment. Besides common or malignant aetiology, rarities should be considered and actively sought. Mesenteric lipoma is a relatively indolent tumour for which early detection can alter clinical presentation.